Ethnocultural diversity of immigrants' personal social networks, bicultural identity integration and global identification. (24th October 2021) - Bobowik, Magdalena; Benet‐Martínez, Verónica; Repke, Lydia
Abstract : There is some evidence that ethnocultural diversity encourages superordinate levels of categorisation, such as feeling identified with people globally. A remaining question is what type of engagement with diversity facilitates this link and why . We use immigrants' personal social network data and examine the link between global identification and ethnocultural diversity among closer relationships (i.e. strong network contacts, such as friendships) and more distant ones (i.e. weak contacts, including neighbours and acquaintances). Furthermore, following exposure to diversity, individuals may internalise more than one culture and differ how they integrate their multiple cultural socialisation into the self (i.e. vary in their degree of bicultural identity integration). We thus test whether relational ethnocultural diversity is linked to a stronger global identification through either cultural blendedness (i.e. combining two cultures) or harmony (i.e. perceiving two cultures as compatible). Relying on a culturally diverse community sample of 216 immigrants residing in Barcelona (53% female, M age = 31 years, SD = 10.4), we found that ethnocultural diversity among strong (but not weak ) contacts was associated with stronger global identification and that this association is mediated by cultural harmony (but not blendedness). These results attest to the link between having ethnoculturally diverse close social relationships and superordinate identification.